FastGarble: an optimised garbled circuit construction framework. (24th September 2021) - Innocent, A. Anasuya Threse; Prakash, G.; Sangeeta, K.
The emerging field of cryptography, Secure Computation, can be used to solve a number of distributed computing applications without loss of privacy of sensitive/private data. The applications can be simple as coin tossing, agreement between parties, or complex as e-auctions, e-voting, private data retrieval for the purpose of carrying out research on sensitive data, private editing on cloud etc. without the help of a trusted third party. For any application, confidentiality can be achieved by the use of conventional cryptographic techniques, but they require the availability data. However, it will not be possible while working with sensitive data, and there arises the need of secure computation. Any protocol on secure computation starts with the construction of garbled circuit of the underlying functionality and, the efficiency of protocol and circuit construction are directly proportional to each other. Hence, as the complexity of application increases, the circuit size increases, resulting in poor efficiency of the protocol, which in turn restricts secure computation from finding its use in day-to-day life applications. In this paper an optimised garbled circuit construction framework named FastGarble is proposed, which has also been shown to improve the time complexity of garbled circuit construction.